Molecular epidemiology, transmission and clinical features of 2022‐mpox outbreak: A systematic review - Nadim Sharif; Nazmul Sharif; Khalid J. Alzahrani; Ibrahim F. Halawani; Fuad M. Alzahrani; Isabel de la Torre Díez; Vivían Lipari; Miguel Ángel López Flores; Md. Anowar Khasru Parvez; Shuvra Kanti Dey (2023)
Abstract Background and Aims The 2022‐mpox outbreak has spread worldwide in a short time. Integrated knowledge of the epidemiology, clinical characteristics, and transmission of mpox are limited. This systematic review of peer‐reviewed articles and gray literature was conducted to shed light on the epidemiology, clinical features, and transmission of 2022‐mpox outbreak. Methods We identified 45 peer‐reviewed manuscripts for data analysis. The standards of the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) Statement and Cochrane Collaboration were followed for conducting the study. Results The case number of mpox has increased about 100 times worldwide. About 99% of the cases in 2022 outbreak was from non‐endemic regions. Men (70%–98% cases) were mostly infected with homosexual and bisexual behavior (30%–60%). The ages of the infected people ranged between 30 and 40 years. The presence of HIV and sexually transmitted infections among 30%–60% of cases were reported. Human‐to‐human transmission via direct contact and different body fluids were involved in the majority of the cases (90%–100%). Lesions in genitals, perianal, and anogenital areas were more prevalent. Unusually, pharyngitis (15%–40%) and proctitis (20%–40%) were more common during 2022 outbreak than pre‐2022 outbreaks. Brincidofovir is approved for the treatment of smallpox by FDA (USA). Two vaccines, including JYNNEOSTM and ACAM2000®, are approved and used for pre‐ and post‐prophylaxis in cases. About 100% of the cases in non‐endemic regions were associated with isolates of IIb clade with a divergence of 0.0018–0.0035. Isolates from B.1 lineage were the most predominant followed by B.1.2 and B.1.10. Conclusion This study will add integrated knowledge of the epidemiology, clinical features, and transmission of mpox.